Mantra Chikitsa in Chaturvisanti Visha Upkrama - A Holistic Approach - Ved Bhushan Sharma,; Ramesh Tiwari, (AYUSHDHARA, 2025)
Ayurveda, the timeless wisdom of life, offers a path to complete well-being. It blends natural healing with inner peace, nurturing the body, mind and soul. In Ayurveda, the treatment of poisoning (Vish Chikitsa) holds a unique and sacred space. Where contemporary medicine zooms into chemicals and molecules, ancient science discovered the subtle energy fields and vibrational medicine through Sacred Chants i.e., Mantra Chikitsa. In Ayurveda, Mantras fall under the category of Daiva Vyapashraya Chikitsa, a spiritual form of therapy. This sacred approach to healing involves practices including the use of mantras, sacred herbs (Aushadhi), wearing of healing gems (Mani dharan), auspicious rituals (Mangal), fasting (Upvasa), scriptural recitations (Svadhyayana) and pilgrimages (Yatra gamana). This article explores the esoteric and potent role of mantras in neutralizing the effects of Sthavar Vish. Through a blend of sound therapy, intention and spiritual discipline, Mantra Chikitsa is believed to purify the body, uplift consciousness and restore Doshic balance. This review explores the fundamental concepts, applications and significance of Mantra Chikitsa in the management of various poisoning conditions and also discusses the psychosomatic benefits of Mantras, correlating ancient wisdom with modern perspectives on vibrational medicine, mind-body harmony and resonance energy effect. With renewed global interest in integrative therapies, Mantra Chikitsa emerges not just as a spiritual practice but a complementary tool in Ayurvedic toxicology.